Do Linear Transformations Preserve Fuzzy Linear Independence? Some Examples - Aristidou, Michael (2012)
In this paper, we examine whether basic linear transformations in R2, such as rotations, scales, etc, preserve fuzzy linear independence. We provide some examples to the contrary.